(untitled) (Journal of Scientific Research, 2011)
This research was aimed to apply the spiroepoxide dithianedioxide for the synthesis of amino acid via ring opening of the spiroepoxide by bis-nucleophiles. First attempt was made to synthesize the bis-nucleophiles, amino alcohol, which was eventually used to the ring opening reaction of the spiroepoxide to produce the morpholine ring compound. The reaction was carried out in racemic and asymmetric method with moderate yield and high 99%. The last step produced amino acid that was still remained unsuccessful. However, it cannot be concluded yet whether the spiroepoxide dithianedioxide is the right intermediate for the synthesis of amino acid. Keywords: Amino alcohol; Morpholine ring; Spiroepoxide dithianedioxide; Amino acid. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: 10.3329/jsr.v3i3.6746 J. Sci. Res. 3 (3), 585-596 (2011)